Advancing Women's Soccer: Interconnected Challenges in Athlete Health and Equity - Colin G. Pennington; Maxwell Premph; Carly Ellman (Athens Journal of Sports, 2026)
Women’s soccer has experienced unprecedented global growth, yet this expansion is shadowed by a high prevalence of anterior cruciate ligament (ACL) injuries and persistent systemic inequities. This exploratory narrative synthesis (2004–2026) aims to bridge the gap between biomechanical risk and social justice by examining the interconnected challenges of injury prevention and equity. The review identifies that female athletes face significant biomechanical vulnerabilities, including increased knee valgus and altered muscle activation patterns, which are exacerbated by "gender-blind" footwear design. Currently, 82% of female players in top leagues report discomfort or pain related to cleats designed for male morphology. Simultaneously, the study explores the underrepresentation of Black women in soccer, highlighting how socioeconomic barriers and chronic underfunding (particularly at Historically Black Colleges and Universities) limit access to elite development. Findings show a staggering resource gap, with average HBCU athletic expenditures ($11M–$12M) dwarfed by those of Power Five institutions ($150M+). The synthesis concludes that addressing these disparities requires an interdisciplinary paradigm shift. Technical innovations, such as the Kofa Agilita women-specific cleat, are presented as essential social interventions. By prioritizing sex-specific biomechanical needs and equitable resource distribution, the sport can foster an environment where athlete health and performance are no longer compromised by systemic neglect. Keywords: ACL injury prevention; footwear biomechanics; Black women’s sport; HBCU athletics